TRANSFER OF HERBAL TECHNOLOGY OF GREEN STEEL LEAVES FOR WHITE IN YOUTH AT 'AISYIYAH ORPHANAGE - Enny Yuliaswati; K Kamidah; Frendy Wibowo (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Background: Vaginal discharge is also known as vaginal discharge. Vaginal discharge is a physiological condition, but because this fluid can make the genital area moist, so often the genital area becomes a good habitat for the growth of various organisms such as bacteria or fungi to thrive. Efforts can be made to make young women more concerned about genital health by providing insight, continuous motivation on the importance of maintaining genital health and direct practice on ways to maintain genital health. Betel leaf contains kavikol can be used as an antiseptic that can kill fungi and germs. Betel leaf boiled water is easy to make, inexpensive, easy to obtain, low risk because it is an herbal medicine, and has been used since our ancestors. Objective: This PKM aims to provide knowledge, personal hygiene practices and train betel leaf stew for young women who live in the Aisyiyah Orphanage, Wirun Mojolaban Sukoharjo Village. Methods: To provide personal hygiene knowledge, it was carried out by providing personal hygiene education counseling using the lecture method for training in the skills of making betel leaf boiled water. Results: Based on the evaluation during community service activities, several positive results were obtained, such as: 1) PKM participants totaled 30 people 2). Participants gave positive feedback. 3) Participants are able to independently make a solution from boiled green betel water to be used to maintain genetic health. The conclusion of this activity is that health education with lectures, discussions and training methods is effective to increase knowledge about how to maintain genital health.Â